Implementasi Deep Learning dalam Meningkatkan Kreativitas Murid melalui Proyek Video Sejarah Lokal Perkotaan di Kelas XI SMA Muhammadiyah 3 Jember - Izzata Fakhreza (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the implementation process of Deep Learning through urban local history video projects and to analyze its effect on the creativity of Class XI students at SMA Muhammadiyah 3 Jember. The study employed a mixed method explanatory sequential design with a quasi-experimental approach, in which Class XI-F (N=25) served as the experimental group receiving Deep Learning-based Project Based Learning (PjBL), while Class XI-D (N=25) served as the control group with conventional instruction. Student creativity was assessed using a rubric with four indicators fluency, flexibility, originality, and elaboration evaluated by two raters with good inter-rater reliability (ICC pretest: 0.834; posttest: 0.865). Results indicate that the implementation proceeded through three PjBL stages: project planning, video production, and presentation and evaluation, with students actively exploring colonial heritage sites in urban Jember as project objects. Quantitatively, the Wilcoxon Signed-Rank Test for the experimental class yielded Z = −4.381 (p < .001), with effect size Cohen's d = 0.876 (Very Large) and N-Gain = 0.476 (Moderate), while the control class yielded N-Gain = 0,192 (Low), confirming that the experimental class showed more optimal improvement. Qualitative findings reinforced these results, as students experienced more authentic learning, utilized technology productively, and gained deeper understanding of local history, with homework completion habits found to correlate with student participation and creativity levels in both classes.
Approved by Teddy
Keywords: Deep Learning; Project Based Learning; Kreativitas; Sejarah Lokal